Being Culturally Sensitive is Not the Same as Being Culturally Competent - Hwang, Wei-Chin; Wood, Jeffrey J. (Pragmatic Case Studies in Psychotherapy, 2007)
Empirically supported treatments have been found to be effective for psychiatric problems among Caucasian American clients. However, there continues to be little research conducted on the efficacy of such treatments when used with ethnic minority clients. Liu (2007) does an excellent job in using cognitive-behavioral and cognitive-interpersonal case formulations to develop an effective treatment plan for TC, a Chinese American male client. Moreover, this case study highlights the importance of cultural competency and cultural adaptation of empirically supported treatments when working with clients from diverse backgrounds. Herein, we summarize the literature on cultural competency and adaptation of therapeutic services, and discuss the cultural complexities involved with treating ethnic minorities.